Role of Interventional Radiology in Managing Primary and Metastatic Breast Cancer - Deipolyi, Amy R.; Ward, Robert C. (Seminars in Interventional Radiology, 2024)
Percutaneous image-guided locoregional therapies are emerging in the treatment of primary and metastatic breast cancer. Cryoablation has emerged as the dominant ablative approach as an alternative to surgery for primary breast cancer in patients who do not wish to have surgery or are poor surgical candidates. Cryoablation is well tolerated and provides excellent local control and cosmesis. Thermal ablation may also be used in the treatment of oligometastatic breast cancer, allowing patients to achieve long disease-free intervals. Transarterial therapies have been studied in the treatment of oligoprogressive hepatic metastasis, though further supportive data would be helpful to demonstrate its efficacy.
Keywords: interventional radiology; breast cancer; ablation; embolization; metastasis